ESTIMATION OF POSTMORTEM INTERVAL USING RGB (RED, GREEN AND BLUE) SCORING OF CORNEAL OPACITY (Journal of Forensic Medicine & Toxicology, 2022)
Introduction : The Estimation of Postmortem Interval (PMI) is one of the fundamental task to be extended by all the forensic experts. The PMI is always calculated taking into consideration of all the postmortem changes in the body. The present study has taken the account corneal opacity in the estimation of PMI using digital photography and software-based scoring method for analysing the images. Material and Methods: This cross-sectional study was conducted at a tertiary health care centre in Western Maharashtra. Total of 100 cases brought to mortuary with known time since death were included in the study. The corneas of the cadavers were photographed and the images were subjected for analysis using the software in terms of RGB Scores. The entire data was analysed using SPSS ver 24.0 for MS Windows. Result : The R, G, B scores of corneal opacity shown a significant positive correlation with each other and PMI. A linear regression equation was derived using the variables for the prediction of approximate PMI.
Keywords: Postmortem interval; Death; Corneal; Opacity; Digital Photography; RGB Scoring